Legal Study of Telemedicine Implementation at XYZ Clinic in South Jakarta Based on the Perspective of Law 17 of 2023 concerning Health - Purnomo, Antonius Dewanto (Penerbit Mandalika Indonesia, 2025)
Telemedicine, as a form of innovation in the healthcare sector, has emerged as an important alternative in providing wider access to medical services. However, the implementation of telemedicine at the practical level still faces various obstacles, including immature regulations, inadequate infrastructure, and limited public awareness and acceptance. XYZ Clinic was chosen because it is located in the dense urban center of South Jakarta so that it can describe a complex urban environment. XYZ Clinic has also implemented telemedicine services. This research studies telemedicine from the perspective of health law, especially Law No. 17 of 2023, where telemedicine involves various aspects including patient data privacy and security, medical practice licensing, medical liability, and regulations related to telemedicine practice. The research method used is Empirical Research using field observations. The researcher makes direct observations of the process or interaction between individuals and the legal system in real and real situations. For example, observation of the object being studied to understand how Telemedicine Implementation at XYZ Clinic in South Jakarta. The conclusion of the Juridical Study of the Implementation of Telemedicine at XYZ Clinic in South Jakarta Based on the Perspective of Law 17 of 2023 concerning Health, shows that the implementation of telemedicine at XYZ Clinic has been in accordance with applicable legal provisions, especially Law No. 17 of 2023 concerning Health. With the right measures in maintaining data privacy, ensuring medical practice licensing, and managing legal risks, XYZ Clinic can provide safe, effective, and compliant telemedicine services.